Urban domestic water supply crisis in the city of Gweru, Zimbabwe - Matsa, Mark; Mavugara, Robertah; Dzawanda, Beauty (Springer, 2021)
The research assessed the urban domestic water supply crisis in Gweru’s Mkoba 19 suburb. The descriptive case study research design was used as it enabled accurate portrayal of the water supply situation in Mkoba 19. Qualitative and quantitative methods of data collection were used incorporating questionnaire surveys, household water quality tests, interviews and field observations. Sixty-four questionnaires were administered to Mkoba 19 residents who were selected through the use of stratified random sampling technique. Purposive sampling was used to select key informants. Convenience sampling was used to select households for water quality sampling. Results revealed that water supply to Mkoba 19 varies within the suburb depending on elevation with the most elevated parts of the suburb hardly receiving any water. The difference between samples tested for coliforms, E. coli, turbidity and residual chlorine collected from Mkoba 19 and the control suburb, Mkoba 16 proved to be significant [p < 0.05; (total coliforms p = 0.03; E. coli p = 0.03; turbidity p = 0.02; residual chlorine p = 0.04)]. The results showed that there is a relationship between intermittent water supply and water quality. Chi square test proved that there was a strong positive association (p < 0.05; p = 0.018) between household income and the type of coping strategy adopted by households. The study recommends the renovation and maintenance of the water distribution system in Gweru to improve the quantity and quality of water supply to Mkoba 19.